Republic of Burundi Fiscal Decentralization and Local Governance : Managing Trade-Offs to Promote Sustainable Reforms - World Bank (Washington, DC, 2015)
This study is highly selective and organized into four thematic chapters. Specifically, chapter 1 provides a snapshot of Burundi’s political and macroeconomic context, and reviews the evolution of the decentralization process to better understand how institutional, political, and bureaucratic dynamics have shaped the historical trajectory of decentralization and generated the outcomes observed today. Chapter 2 provides a systematic investigation of the status of fiscal decentralization in Burundi, and identifies key policy issues to be considered to ensure the medium-term sustainability of the reform process while at the same time addressing the short-term financial needs of communes. Chapter 3 provides an in-depth diagnostic of a key service delivery responsibility recently devolved to communes—the provision of land registration services—and discusses the challenges and opportunities related to ongoing efforts to scale up access to these land services across 116 rural communes and Bujumbura. Chapter 4 shifts the focus to the nature of statecitizen relations in an effort to better understand how citizen engagement in the decision-making process may be improved and local authorities held accountable for the provision of basic services.